Historical Dictionary of Heidegger's Philosophy - Schalow, Frank (Historical Dictionaries of Religions, Philosophies, and Movements Series., 2019)
This third edition of Historical Dictionary of Heidegger's Philosophy, Third Edition contains a chronology, an introduction, appendixes and an extensive bibliography. The dictionary section has over 800 cross-referenced entries that provides a clear and comprehensive exposition of the key developments in his life and his thought.